Caracterização florística, fitossociológica e análise da relação entre a distribuição das espécies e a distância da margem de riachos intermitentes na bacia hidrográfica do rio Taperoá, semi-árido paraibano, Brasil - Lacerda, Alecksandra Vieira de (Universidade Federal de São Carlos, 2007)
The general aim of this study was to establish floristc and phytosociological characteristics of three riverine areas and to analyze the relationship between the distance from the edge of the water and the distribution of the bushlike and arboreous species in the hydrographic basin of the river Taperoá, in the semi-arid region of the state of Paraíba. The research was developed from january/2004 to june/2006 and comprehended riverine areas of the intermittent streams of Cazuzinha (7026 13 S and 36054 30 W; altitude 564-579 m), Mares (7031 53 S and 36033 39 W; altitude 536-550 m) and Farias (7025 33 S and 36029 21 W; altitude 454-470 m). The work of research has taken the following steps: 1) floristic survey of the bushlike and arboreous stratum and analysis of similarities between the sample observed in the area and other studies also developed in the basin of the river Taperoá; 2) characterization of phytosociological structure and 3) analysis of the relationship between the distance of the specimens from the three water courses and their floristc and phytosociological variations. In the first stage, nonsystematic collection of samples of the vegetation has been done monthly. For the second and third stages, 51 contiguous parcels of 10 X 20 m (1.02 ha) have been established for each area, distributed in three parallel strips of land along each course of water. Were measured standing specimens, alive or dead, whose trunk measured ≥ 3 cm of diameter at ground level (DNS) and whose total height was ≥ 1 m. In the floristic survey of the three areas, a total of 91 species was registered, of which 68 occurred in the area of the stream Cazuzinha, 62 in the stream Mares and 56 in the stream Farias. The families present in higher number of species and genuses were Euphorbiaceae, Fabaceae, Mimosaceae, Caesalpiniaceae and Rubiaceae. Of the total of species registered for the three areas, 16 are present in the known lists of riverine bushes in other states of Brazil, 26 are endemic of the Caatinga (Brazilian northeastern savanna) and 13 of them had been exclusive of the researched area. The floristic analysis of similarities between the studied areas and the results of five other surveys indicates that floristic similarity between areas is related the geographic distance and characteristics of human occupation and use of the land. For this phytosociological survey, a total of 5,840 specimens have been observed, 5,126 of them alive specimens and 714 dead but still standing. 2,138 of the total observed specimens in the riverine vegetation of the stream Cazuzinha (2,096 individuals.ha-1), 1,838 in the stream Farias (1,802 individuals.ha-1) and 1,864 in the stream Mares (1,827 individuals.ha-1). The total basal area of riverine vegetation of the streams of the Cazuzinha, Farias and Mares were 25.4 m2.ha-1, 15.6 m2.ha-1 and 14.5 m2.ha-1, respectively. Considering each stream particularly, the three more important species in VI were: Aspidosperma pyrifolium, Combretum pisonioides and Caesalpinia pyramidalis (Cazuzinha) and Caesalpinia pyramidalis, Combretum leprosum and Croton sonderianus (Farias and Mares). The average height and diameter of the measured individuals were respectively: 5.4 m and 12.4 cm (Cazuzinha), 3.9 m and 10.5 cm (Farias) and 4.8 m and 10.1 cm (Mares). The values of diversity and equability have been respectively: 2.61 nats.ind.-1 and 0.66 (Cazuzinha), 2.18 nats.ind.-1 and 0.59 (Farias) and 2.77 nats.ind.-1 and 0.72 (Mares). The analysis of the relationship between the distance of the edge of three streams and floristic and phytosociological variations showed that the factor distance is determining for floristic wealth, once, in three environments, the first strip (Closest to stream) is responsible for the highest values in the species quantity. Some of these have occurred exclusively or preferentialy in one or two of the strips while other occurred in the three of them. Among the 10 higher Values of Importance (VI), it was observed that only Caesalpinia pyramidalis, Combretum leprosum and the dead category were present, in different hierarchical positions of VI, in all the strips of the three studied areas. Generally, the first strip (Closest to stream) distinguished itself of the other two (Halfway and Furthest from stream) for the highest total density and total basal area. In the case Cazuzinha and Farias, the values of diversity decreased from Closest to stream towards Furthest from stream; the inverse, however, occurred in the stream Mares where the values diminished from Furthest from stream to Closest to stream. The observed data of average height and diameter, with some exceptions, showed that Furthest from stream presented lesser values when compared to Closest to stream and Halfway. Therefore, we can conclude that the distance from courses of water, possibly depending on water contained in the ground, is one of the main factors that define distribution of the species in space. However, this study indicates the importance of more research in areas of Caatinga, aiming to confirm if the tendential preferences of the species, observed in the present study, are repeated in other conditions.
Keywords: Botânica; Florística; Vegetação ribeirinha; Caatinga; Comunidades vegetais; Relações espécie-ambiente; Floristic; Structure; Species-environment relations; Riverine vegetation; Caatinga; CIENCIAS BIOLOGICAS::ECOLOGIA